Patients with rare diseases: from therapeutic orphans to pioneers of personalized treatments - Christoph Klein; William A Gahl (EMBO Molecular Medicine)
Abstract Common diseases, such as cancer, diabetes mellitus, or Alzheimer's disease, affect a large segment of the population, which justifies the enormous financial allocations for translational and clinical research. In contrast, the ~5,000 known rare disorders affect only very few patients each, even though the cumulative disease burden is substantial. This influences not only the general appreciation of research to address rare diseases, but also the allocation of research funds. Importantly, however, studying rare diseases has contributed enormously to our understanding of human biochemistry, cell and developmental biology, and physiology. For example, Linus Pauling and Vernon Ingram's discovery of a structural difference and amino acid variant in the beta‐globin protein, which causes monogenic hemoglobinopathies such as sickle cell disease or thalassemia, issued in the era of molecular medicine (Pauling et al, 1949). Subsequently, numerous genetic defects in critical genes controlling differentiation and/or function of cells and organs have been identified and opened new possibilities for molecular diagnosis.